Pemanfaatan Effective Microorganisms 4 (EM4) Menggunakan Media Biofilm untuk Menurunkan Amonia dan Fosfat pada Limbah Cair Rumah Sakit - Sitti Badrah; Resti Putri Aidina; Andi Anwar (Universitas Faletehan, 2021)
Waste water that produced by hospital activities is one of the most potential sources of water pollution because it contains high levels of organic compounds, hazardous chemical compounds, radioactivity, and microorganisms that are harmful to the environment and health. This study aims to determine the difference in decreasing ammonia and phosphate levels by utilizing Effective Microorganisms 4 (EM4) using biofilm media in waste water at Atma Husada Mahakam Mental Hospital. This research is a quasi-experimental study with non equivalent control group design. Sample of research consisted by 1 control tub and 2 reactors. In the anaerob-aerob tub, there is a PVC-based biofilm media. Waste water is flowed continuously with detention time in 2 weeks, 3 weeks, and 4 weeks. The results showed the average reduction in ammonia levels with the addition of 5% EM4 is 92,5% and 10% EM4 is 92,1%. Meanwhile, the average reduction in phosphate levels with the addition of 5% EM4 is 92,19% and 10% EM4 is 65,56%. This study statistically shows there is no difference in the ammonia levels reduction (P value > α or 0,941 >0,05) and there is a difference in the phosphate levels reduction (P value < α or 0,0001 < 0,05).